"Between a Rock and a Hard Place": The Coronavirus, Livelihoods, and Socioeconomic Upheaval in Harare's High-Density Areas of Zimbabwe. Issue 3 (September 2021) - Makombe, Eric Kushinga
For Zimbabwe, the confirmed Covid-19 deaths for 2020 numbered in the hundreds, not thousands. Still, Covid-19 could not have come at a worse time owing to a myriad of crises the country was going through. As a result, the Covid-19 pandemic was much more than a public health crisis as it threatened already vulnerable people, putting lives and livelihoods at risk. This article focuses on the socioeconomic impact of the novel coronavirus pandemic, examining the social pattern of its unfolding and impact, analyzing the institutional and communal responses to the disease, and marking the effects of its aftermath in Harare's high-density residential spaces. The research design captures a broad empirical picture of what was happening by specifically drawing on case study examples from Harare, the capital city of Zimbabwe. The broad objective of the research brings out how low-income households experienced the Covid-19 pandemic compared to higher-income households as informed by sex-based differences, access to healthcare, and food. It also captures the differential impacts and inequalities in socioeconomic outcomes, livelihoods, poverty reduction, and human development informing these household experiences. Beyond this, the study captures and highlights how the Covid-19 crisis led to widespread instances of food insecurity, economic anxiety, and general disenfranchisement from alternative sources of income that, in turn, created further social upheaval. The last strand of this article exposes the implications of some of the public health measures instituted in attempts to tackle Covid-19.